HUBUNGAN ANTARA KADAR KALSIUM DENGAN SERANGAN ASMA PADA ANAK - Rompies, Ronald; Sumampow, Christine; Wahani, Audrey (JURNAL BIOMEDIK : JBM, 2016)
Abstract: Asthma is a chronic inflammatory disorder of the respiratory tract that can cause an increased response and activity within the airway which is characterized by the recurrent episodes of wheezing, shortness of breath, and cough accompanied by airway obstruction in varying degrees. Vitamin D plays a role in the pathogenesis of asthma. Many studies suggest a relation between vitamin D and calcium, which can be seen as a possible link between calcium levels and asthma. This study aimed to determine the correlation between the level of calcium and asthma attacks in children. This was a case-control study that gathered 21 asthmatic children and 19 non-asthmatic children with acute respiratory infections who did not use corticosteroids for the treatment at outpatient services Prof. Dr. R. D. Kandou Hospital Manado from January to June 2015. Calcium levels of asthmatic patients and non-asthmatic were noted. Statistical analysis using logistic regression with a P value < 0.05 were considered significant. The results of logistic regression analysis showed a significant association between calcium level and asthma attack (P = 0.04 with OR = 2.75). The average level of calcium in the asthmatic group was 9.2 mg/dL (0.81, 95% CI 8.91 to 9.64) and the non-asthmatic group was 8.7 mg/dL (0.72, 95% CI 8.38-9.07). Conclusion: There was a correlation between calcium level and asthma attack in children. The lower the level of calcium, the higher the chance of asthma attack.Keywords: children, asthma, calciumAbstrak: Asma adalah kelainan inflamasi kronis saluran pernapasan yang dapat menyebabkan peningkatan respon dan aktivitas jalan napas, ditandai dengan episode mengi berulang, sesak napas, dan batuk yang disertai obstruksi jalan napas dalam derajat bervariasi. Vitamin D berperan dalam patogenesis asma. Banyak penelitian mengatakan bahwa terdapat hubungan antara vitamin D dan kalsium, sehingga diduga adanya hubungan antara kadar kalsium dan asma. Penelitian ini bertujuan untuk mengetahui hubungan kadar kalsium dengan serangan asma pada anak. Jenis penelitian ialah kasus kontrol dimana dikumpulkan 21 anak dengan asma dan 19 anak non-asma dengan infeksi saluran napas akut dan tidak menggunakan kortikosteroid yang datang berobat di pelayanan rawat jalan RSUP Prof. Dr. R. D. Kandou Manado dari Januari sampai Juni 2015. Kadar kalsium pasien asma dan non-asma dicatat. Analisis statistik menggunakan regresi logistik dengan nilai P < 0,05 dianggap bermakna. Hasil analisis regresi logistik menunjukkan hubungan bermakna antara kadar kalsium dengan serangan asma (P = 0,04 dengan OR = 2,75). Rerata kadar kalsium pada kelompok asma 9,2 mg/dL (0,81, 95% CI 8,91-9,64) dan kelompok non asma 8,7 mg/dL (0,72, 95% CI 8,38-9,07). Simpulan: Terdapat hubungan antara kadar kalsium dan serangan asma pada anak. Makin rendah kadar kalsium, makin tinggi peluang terjadinya serangan asma.Kata kunci: anak, asma, kalsium